Early and long-term outcomes of pericardiotomy in the treatment of primary cardiac tamponade - Perek, Bartłomiej; Tomaszewska, Iga; Stefaniak, Sebastian; Bartczak, Agnieszka; Jemielity, Marek (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2015)
Introduction : Cardiac tamponade is a life-threatening clinical entity that requires emergent treatment. A variety of therapeutic methods have been applied. The purpose of this retrospective analysis was to study the efficacy of emergent surgical pericardiotomy in both the relief of cardiac tamponade and in the prevention of recurrence of pericardial effusion. Material and methods: This study involved 90 consecutive patients (58 males and 32 females) with a mean age of 57.4 ± 14.1 years, who underwent emergent pericardiotomy in the years 2006 to 2011 due to symptomatic primary cardiac tamponade. At the end of the follow-up period all living subjects had control echocardiographic examination. Survival analysis was performed with the use of the Kaplan-Meier method. Results : The mean duration time of surgery was 14.2 ± 4.5 minutes. All patients survived surgery but one died during in-hospital stay. During the post-discharge follow-up period (median 49 months) 32 patients died for any reason. One-year and four-year probability of survival was 0.68 ± 0.05 and 0.64 ± 0.05, respectively. Malignancy diagnosis was associated with significant negative impact on survival. One-year and four-year probability of survival was 0.56 ± 0.06 and 0.53 ± 0.06 for cancer patients while it was 0.93 ± 0.05 and 0.89 ± 0.06 for the others, respectively. In two cases, only cancer patients, re-intervention due to effusion recurrence was necessary. Conclusions: Pericardiotomy, although invasive, is a safe method to relieve cardiac tamponade. It is also very efficient in the prevention of recurrence of pericardial effusion, even in cancer patients.